Открытая измерительная площадка - Животов, Н. Д.; Немченко, Юрий Семенович; Сараев, А. И. (НТУ "ХПИ", 2009)
Створено майданчик для вимірювання напруженості поля індустріальних радіозавад в смузі частот від 9 кГц до 1 ГГц, який повністю відповідає вимогам міжнародного стандарту CISPR-16-1-1999.

Area for measurement of the tension of the field industrial radio disturbances in band of the frequencies from 9 kHz to 1 GHz is created, and she completely meets the demands of international standard CISPR-16-1-1999.
Keywords: индустриальные радиопомехи; ОИП; проводящая поверхность; приемные антенны